Comprehensive preparation and catalytic activities of Co/TEMPO-cellulose nanocomposites: A promising green catalyst. (1st November 2022) - El Idrissi, Nouaamane; Belachemi, Larbi; Merle, Nicolas; Zinck, Philippe; Kaddami, Hamid
Abstract: A green method for the production of cobalt/(TEMPO-Cellulose) aerogel heterogeneous catalyst was developed. The preparation implied the reduction of CoSO4 by NaBH4 in TEMPO-Cellulose water dispersion in ambient conditions. The formation of Cobalt nanoparticles is due to the presence of "TEMPO-Cell" which screens the Co 2+ ions and prevents their combination with boron. SEM, XRD, EDX, FTIR, TEM and XPS were used to analyze the structure of the catalyst and showed that metallic cobalt particles have nanometric size and are well dispersed in the aerogel. The catalyst showed excellent activity for model reactions such as the reduction of 4-nitroaniline, 4-nitrophenol and 2-nitrophenol in water, in the presence of NaBH4 . The reaction kinetic was studied by UV–visible spectroscopy, which showed that this catalyst is efficient to achieve 100 % reduction with high reaction rate and turnover frequency. The aerogel catalyst was reused more than ten times without significant loss of its catalytic activity. Highlights: "Cobalt(0)/TEMPO oxidized cellulose" heterogeneous catalyst was prepared. The characterizations have shown nanometric size and good dispersion of Co 0 particles. A screening effect of TEMP-Cell, which prevent CoB components formation, was highlighted. High catalytic performances have been shown for the reduction of nitro to amine groups. The catalyst retains catalytic activity even after 11 cycles without significant loss of its catalytic activity.